Politik dan Bisnis di Tingkat Lokal: Studi Kasus Relasi Penguasa dan Pengusaha Pada Eksploitasi Tambang Biji Besi di Bima - Jufriansyah, Jufriansyah (IAHN Tampung Penyang Palangka Raya, 2025)
Abstract This study was conducted to analyze the contestation of interests and relations between local government and entrepreneurs in natural resource management, particularly iron ore mining policy in Bima. The study used a qualitative descriptive method. Primary and secondary data were used to analyze the relationship between the Bima Regency Government and iron ore mining entrepreneurs. The findings of this study show the form of relations between the Bima Regional Government and the granting of permits to businesspeople to invest in Bima despite opposition from the community living in the mining location.